Hermeneutika Al-Qur’an Muhammad Talbi (Socio-Historical Hermeneutics) (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2018)
This article discusses briefly about Mohammed Talbi’s modern interpretation of holy Qur’an. Two main ideas in his interpretation are: Talbi emphasizes on historical and humanist approach in reading Qur’an, that place great hermeneutical value on a historical context. The historical approach reads the Qur’an in light of the historical context in which the Qur’an was revealed. He also emphasizes, in addition to the first approach, on the maqasid approach, that the interpreter should understand the intentions of the text, to find something beyond the text, as the epistemological-hermeneutical ways to trace the foundation, spirit, and philosophical framework of the historical text, in order to be situated within todays context. In making cases of the approach, Talbi give example of the interpretation of An-Nisa: 34-35, that contains of the education ways of husband toward his wife. He refuses, with the contextual reading and making sense of the Arab tradition when the revelation of this text, the justification of awful ways of treating the wife, that irrelevant for the contemporary democratic society.